THE USE OF ENGLISH LINGUISTIC LANDSCAPE IN PALANGKA RAYA CITY (PENGGUNAAN BAHASA INGGRIS DALAM LANDSKAP LINGUISTIK DI KOTA PALANGKA RAYA) - Rensi Sisilda; Maria Arina Luardini; Natalina Asi; Eliza I (Universitas PGRI Sumatera Barat, 2022)
This study discusses the use of English in the linguistics landscape in Palangka Raya city, Central Kalimantan. English is used as an international language, it is not just a means of communication, but it must also obey the rules and correct language. Then, linguistics landscapes are all open areas in Palangka Raya that are generally open and accessible to everyone. It has a function in the cities. The purpose of the study was to describe the practical use of the English linguistics landscape in the city of Palangka Raya, according to the texts from signboards, billboards, and posters in Palangka Raya. Data were collected by observation and interviews. The data were analyzed by referring to the literature review and looking at the function of language. In fact, after analyzing the use of English in the linguistics landscape, some texts did not comply with the rules, especially errors in spelling. Then, the researcher found two kinds of English language functions in using the English language linguistics landscape in Palangka Raya city, such as informative and interactive uses.